Assessment of nurses’ knowledge about therapeutic play in pediatric services of a training and research hospital - Ayşenur TAŞÇI; Selen OZAKAR AKCA (Universa Medicina)
Background Hospitalization disrupts children’s lives and can produce feelings of anxiety, fear, or pain. Playing is an important part of children’s lives.It is necessary for nurses to provide holistic and quality care, including therapeutic play, which contributes to the recovery of children by relaxing them both physically and emotionally. The aim of this study was to determine the level of knowledge of pediatric nurses about therapeutic play and find out the relations of therapeutic play with nurses’age, educational level, marriage status, and length of employment.